Ellipsoidal mixture models for clustering: an application to web-based education data - Jafreen, Saujanna; Mallick, Taslim S; Khan, Jafar A (Bangladesh Journal of Scientific Research, 2016)
This study considers the Gaussian mixture models for clustering. Since spherical and diagonal models occur very rarely in practice and analysis can be simplified when these models are implemented, we focus on the ellipsoidal models. EM algorithm is used to fit these models to a real data set related to an adaptive educational electronic course. Misclassification rates and Bayesian Information Criteria (BIC) values are used for comparison. Bangladesh J. Sci. Res. 28(1): 1-7, June-2015